Virtual Communication in A Hybrid Workplace: Impact on Team Effectiveness - Yosaphat Danis Murtiharso (Journal of Dialogos, 2025)
Hybrid work arrangements have transformed communication and collaboration systems in organizations, particularly in Indonesia where digital transformation accelerated rapidly during the pandemic. Virtual communication has emerged as the main mechanism for coordinating tasks, sharing knowledge, and maintaining interdependence among geographically distributed team members. This study employed a systematic literature review approach to examine the role of virtual communication, digital leadership, and organizational culture in shaping team effectiveness within hybrid workplaces in Indonesia. Findings indicate that balanced synchronous–asynchronous communication, clarity of expectations, and psychological safety enhance collaborative performance, whereas communication overload and unequal digital readiness hinder productivity. Furthermore, leaders who adopt empathetic, coaching-based, and outcome-oriented approaches foster stronger engagement and trust in hybrid teams. Organizations that develop adaptive communication norms, invest in digital capability building, and implement equitable hybrid work policies tend to achieve higher team cohesion and performance. This study highlights the importance of integrating technological, human, and cultural dimensions to optimize hybrid work effectiveness in emerging economy contexts